PSX-19 Effects of yeast fermentation products on performance and serum metabolites of beef cattle grazing warm season pastures. (7th December 2018) - Rivera, J; Johnson, J; Lutz, A; Vann, R; Tipton, P
Abstract: Yeast fermentation products (YFP) are thought to have a positive effect on response to heat stress in beef cattle, therefore an experiment was conducted to determine the effects of YFP on performance and serum metabolites in cattle exposed to a heat stressed environment. Twenty four Bos indicus/Bos taurus crossbred steers (BW = 274.3 ± 23.3 kg) were blocked according to initial body weight, then randomly assigned to treatment. Both treatments received 1% of their BW as a commercially available feed supplement, while grazing warm season bahiagrass pastures (n=8 pastures per treatment), during the summer months in southern Mississippi. Cattle fed YFP received 10 g per animal daily of Saccharomyces cerevisia blended in the supplement, while control (CON) simply received the supplement. On d 0, 28, and 56, cattle were weighed and blood samples were collected via jugular venipuncture for subsequent analysis of SUN and glucose. The addition of YFP did not affect BW ( P > 0.05), ADG ( P = 0.23) and total kg gained during grazing ( P = 0.22). Nevertheless, feeding YFP tended to increase serum glucose at d 28 ( P = 0.06; 41.2 vs 47.7 mg/dL for CON and YFP, respectively) and significantly increased serum glucose ( P = 0.05) at d 56 (51.2 and 58.1 mg/dL for CON and YFP, respectively). No effects of YFP ( P > 0.81) were noted with regards to SUN at any time during the study. Results suggest that YFP might have an effect on glucose metabolism, but did not affect performance.